2018
DOI: 10.1002/ece3.4176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ecological redundancy on the performance of machine learning classifiers in vegetation mapping

Abstract: Vegetation maps are models of the real vegetation patterns and are considered important tools in conservation and management planning. Maps created through traditional methods can be expensive and time‐consuming, thus, new more efficient approaches are needed. The prediction of vegetation patterns using machine learning shows promise, but many factors may impact on its performance. One important factor is the nature of the vegetation–environment relationship assessed and ecological redundancy. We used two data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Our study did identify some of the environmental factors as important drivers, but, on the whole, the unexplained variability remained very high. These assertions find additional support through Macintyre, Van Niekerk, Dobrowolski, Tsakalos, and Mucina () who implemented spatially explicit modelling to demonstrate the high predictability of well‐structured vegetation‐environment relationships of the Northern Kimberley woodlands compared to our Eneabba kwongan data. Therein, Macintyre et al.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study did identify some of the environmental factors as important drivers, but, on the whole, the unexplained variability remained very high. These assertions find additional support through Macintyre, Van Niekerk, Dobrowolski, Tsakalos, and Mucina () who implemented spatially explicit modelling to demonstrate the high predictability of well‐structured vegetation‐environment relationships of the Northern Kimberley woodlands compared to our Eneabba kwongan data. Therein, Macintyre et al.…”
Section: Discussionsupporting
confidence: 64%
“…Therein, Macintyre et al. () found that the vegetation of Eneabba was difficult to spatially separate owing to the high redundancy of the environment‐vegetation relationship, particularly true at the Community spatial scale. We, therefore, hypothesised that processes other than ecological sorting, albeit working along long‐term evolutionary scales lead to the formation of vegetation structures showing poor correspondence with the current ecological fabric of the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Spatially explicit modelling of that system also found a weak relationship (low predictability) between the vegetation and the environment when compared to the Northern Kimberly Eucalyptus Woodland which was well structured along environmental gradients (Macintyre et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This mapping was done in times where the only accessible remote-sensed data were aerial photos. The world of vegetation mapping has long moved on and embraced tools such as the use of vegetation plot data and formalised classifications, satellite imagery interpretation, and machine-learning based predictive modelling (Mucina & Daniel 2013;Macintyre et al 2018).…”
Section: Problemsmentioning
confidence: 99%
“…The maps of PNV can have limitations. For example, in the production of maps B and C (Macintyre et al 2018), it was shown that at the coarse scale, the predictions were robust, while at the finer scales, additional factors of ecological redundancy made these predictions unreliable. In contrast, map D shows a supervised per-pixel classification of the vegetation of the area using multi-temporal, remotely sensed data from the Sentinel 2 platform (equivalent to ~ 1:12,500 scale) which returned a highly reliable classification.…”
Section: Problemsmentioning
confidence: 99%